Recidivism Rates Among Biological Fathers and Parental Figures Who Commit Child Sexual Abuse in Hawai'i - Dixon, Stephanie Dixon (2018)
Sex offenders are commonly grouped into categories based on the characteristics (e.g., victim age, relationship to offender) of their victims for criminal sentencing and treatment purposes. The purpose of this quantitative, quasi-experimental study was to address the gap in the lack of literature comparing recidivism rates among biological fathers and male parental figures who committed incestuous child sexual abuse in Hawai'i against children 15 years or younger. This study was the first attempt in the state to examine the number of inmates who had completed their maximum sentences and were later returned to prison for new felony incest offenses. Secondary data were obtained from the Safety Sex Offender Treatment Program (SOTP) within the state of Hawai'i Department of Public Safety (DPS) from the years 1988 to 2013. Areas of recidivism and crimes involving biological fathers, stepfathers, boyfriends of the victims' mothers, foster parents, and hana'i family members were included (N = 1,727). Three hundred and ten met the criteria for the current study. The study had 2 independent variables: the offender's relationship to the victim (e.g., biological, adoptive, stepparent, foster parent or hana'i family members); or the residency status of the offender (e.g., lived with the victim versus did not live with the victim). The dependent variable was the recidivism rates of the incest offenders (i.e., new incest offense convictions). Analysis of these variables using the ï?£2 with Cramer's V statistical test lacked statistical significance as there was no documented evidence of recidivism in either group. The potential for social change and clinical significance still exists. Further analysis of the effectiveness of the SOTP may aid in sustaining low recidivism rates